Teaching monetary theory and monetary policy implementation after the crisis - Marc Lavoie (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2015)
The author reflects on the state of macroeconomic theory, and more specifically on how monetary economics is being taught in the aftermath of the global financial crisis. Whereas heterodox macroeconomic theory is very much alive due to the influx of a large number of contributions and contributors, the latter still have a hard time finding positions in the academic world, as journal and departmental ranking exercises have restricted so-called standards of excellence to the neoclassical approach. The crisis has not yet induced mainstream economists to open up to different approaches that put more emphasis on realistic features than on imaginary ones based on neoclassical micro-foundations. As an exemplar, the chapters on money and banking in two first-year textbooks are being examined, an orthodox one by Greg Mankiw and a heterodox one by Neva Goodwin et al. Unsurprisingly there is little to be learned about the crisis from Mankiw's book, while the book by Goodwin et al. devotes a large amount of space to the causes and consequences of the crisis. Still, Goodwin and her co-authors are not heterodox enough: they are less heterodox than a number of central bankers when it comes to a number of key features of monetary theory.
Keywords: A11; A2; E5; 330; teaching economics; realism; DSGE models; fractional-reserve banking; post-Keynesian economics